Physical, chemical and microbiological analysis of the water quality of Rawal Lake, Pakistan (International Journal of Agricultural Research, Innovation and Technology, 2014)
What better gift of nature would be than good quality water? In order to assess the quality of water of Rawal Lake, following research was carried out. Rawal lake is a source of drinking water supplied to many areas of Rawalpindi and Islamabad the capital city of Pakistan. Water of this lake is being highly polluted by the local communities alongside the lake through solid waste dumping. Samples of surface water were collected, tested and analyzed in the laboratory on the basis of physical, chemical and microbiological parameters. The results showed uncertainties in many of the selected parameters. Microbiological analysis revealed high contamination of E. coli, fecal coliform and total coliform in the samples proving it unfit for drinking. It was found that the concentration of all physical parameters such as nitrates, chloride, pH and conductivity were within the normal limits. The level of heavy metals like lead, iron, chromium etc. was also found low. Turbidity at some points exceeded the maximum acceptable limit as per WHO statement. DOI: http://dx.doi.org/10.3329/ijarit.v4i1.21087 Int. J. Agril. Res. Innov. & Tech. 4 (1): 28-31, June, 2014